Health Education in The Parameter of Physical in Primary and Secondary Schools - LIU, GENPING; Fernando, Yudi (International Journal of Innovation Research in Education, Technology and Management, 2024)
This study aims to investigate the impact of health education integrated within physical education curricula in primary and secondary schools on students' overall well-being and health-related behaviours. After a comprehensive review of the extant literature and empirical studies, the seeks to explore the significance of incorporating health education components, such as nutrition, fitness, personal hygiene, mental health, and substance abuse prevention, into physical education programs. Findings from the study consistently demonstrate that integrating health education into physical education classes leads to notable improvements in students' knowledge and awareness of health-related topics, positive changes in attitudes towards physical activity, and the development of essential life skills crucial for promoting lifelong wellness. Furthermore, this study highlight the implications of the research findings for educators, policymakers, and stakeholders in enhancing the effectiveness of health education initiatives within physical education curricula to address public health concerns and promote healthy behaviours and attitude among students in primary and secondary schools.